CEO Duality and Financial Performance During COVID-19 - Dahlia, Renata; Permatasari, Yani (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
This study aims to investigate the impact of CEO Duality on financial performance by examining manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. With a sample size of 844 companies selected based on specific criteria, data were collected from annual reports and audited financial statements. Utilizing multiple linear regression for analysis, the research findings suggest that CEO Duality does not significantly affect financial performance, both pre- and during the Covid-19 pandemic. However, its presence raises concerns about the independence of a company's board of directors, potentially influencing financial outcomes. The study concludes that CEOs and boards of commissioners demonstrate an understanding of their roles in achieving the company's objectives.